Antonomasia in English and Arabic: A Contrastive Study - Assist. Lect.Daniah AbdulAmeer Al-Assam; Prof. Dr. Hameed Hassoon (Periodica Journal, 2022)
This contrastive study deals with the word formation process of antonomasia in both English and Arabic respectively. The main focus of this study is to investigate the expansion on the meaning of utterances in both English and Arabic. The basic and explicitly adoptive linguistic phenomenon responsible for this expansion is antonomasia in English and its counterpart كناية, نعت in Arabic. The study sheds the light on the similarities and differences of this phenomenon in both language systems. It will also focus its resources and classifications in both languages. The study also aims at investigating the purposes behind using antonomasia in the languages under investigation. Among the major similarities concluded from this contrastive analysis is the fact that this phenomenon is explicitly existent in both English and Arabic, in addition to the features of turning a proper noun or epithet to the meaning of the well-known word. Moreover, in both languages, the resources of this phenomena antonomasia is depend on the deep literary, religious and historical origins. Therefore, during the process of translation finding an equivalent endangers the meaning. With regards to the major differences concluded from contrasting the two languages, on the one hand English antonomasia focuses heavily on names of literature while Arabic antonomasia depends on verbs and acts. In Arabic, there is an additional mechanism for creating antonomasia which depends on collocation in utilizing the metonymic meaning.
Keywords: Antonomasia; Metonymic; Metaphorical